Network Pharmacological Analysis on Arteriosclerotic Cardiovascular Disease Prevention of Walnut Kernels - XU Zi-wu; HUI Jia-ru; WU Xi-wen; DENG Xiao-lei; MENG Lei (Liang you shipin ke-ji, 2022)
In this study, network pharmacology and molecular docking methods were used to explore the mechanism of components in walnut kernels in preventing atherosclerotic cardiovascular disease (ASCVD). Thirty-four main active components of walnut kernels were screened by TCMSP and their potential targets were predicted using the SwissTargetPrediction database. ASCVD-related targets were screened by the Genecards, OMIM and DRUGBANK databases. The STRING database and Cytoscape software were used to build a protein-protein interaction (PPI) network map to extract core targets. GO enrichment and KEGG pathway analysis of potential targets were performed using Metascape database. The enrichment analysis found that walnut kernel could play a role in regulating PPAR signaling pathway, adhesion junction, platelet activation, regulation of lipolysis in adipocytes and other signaling pathways. Molecular docking technology verified that the key components (quercetin, myricetin, ellagic acid, kaempferol) had good binding activity to core targets (AKT1, EGFR, SRC, CCND1, ERBB2). This study showed that walnut kernel might play a role in delaying ASCVD by regulating cell proliferation and inflammatory response.